A thiirane linker for isopeptide mimetics by peptide ligation. Issue 19 (11th May 2016) - Kawakami, Toru; Mishima, Yuichi; Kinoshita, Misaki; Lee, Young-Ho; Suetake, Isao
Graphical abstract: Highlights: A method for introduction of an isopeptide-mimetic structure is proposed. 2-Aminomethylthiirane can be used as a linker for peptide ligation. Ubiquitinated histone proteins can be synthesized. Abstract: 2-Aminomethylthiirane was used to attach a 1, 2-amino-thiol moiety at thiol groups of peptides for use in peptide ligation to produce isopeptide mimetics. To confirm the strategy, a ubiquitinated histone H3 peptide was prepared, and the ubiquitin was correctly folded judging from CD spectra with no influence by the random H3 peptide.